47-Year-Old Man with Quadriplegia Following Traumatic Spinal Cord Injury in the Cervical Spine: A Case Report - Dziedzic, Mariola Maria; Pach, Magdalena; Nowak, Agnieszka; Dobrzańska, Justyna; Partyka, Alicja; Michalczewska, Aneta; Fugas, Agnieszka; Wierzejska, Natalia; Chmielowiec, Zuzanna; Smykiewicz, Karolina (Journal of Education, Health and Sport, 2024)
Spinal cord injuries (SCIs) typically affect young, healthy males, with the cervical spine being the most frequently injured area. These injuries are devastating and have a lifelong impact on a person's health and well-being. While uncommon, SCIs can occur during sports participation, as seen in this case study. This case examines a 47-year-old male skier who sustained a skiing accident and presented with quadriplegia upon arrival at the trauma centre. It highlights the critical role of readily available diagnostic imaging and efficient teamwork within trauma centres in managing such complex injuries.